A temática sexualidade no contexto escolar:diagnóstico situacional da região leste de Goiânia, Goiás - CHAVEIRO, Laine Gomes (2011)
Cross-sectional study with directors and teachers in public schools, municipal and state institutions in the Eastern Region of Goiânia-GO, conducted between April/May 2009 in order to investigate the insertion of the sexuality issue in the school context. Participants were interviewed and the Political Pedagogical Projects (PPP) analyzed. Data were analyzed using Epi-info 6.04. The results showed that every PPP are current and topics covered, but not in cross-sectional way, as recommended by the National Curricular Parameters (NCP), the majority of content worked exclusively in the discipline of biology. Of the 79 teachers interviewed 35.4% were from municipal and 64.6% state network. Of these 50% were under 35 years, 68.4% were female and 40.5% were married. Many have reported having no background in dealing with the theme (75%) in municipal (86.3%) in the state schools, the same as (39.3%) and (27.4%) respectively said they had no experience in this area. More than half reported that the age for discussing the issue is before 12 years (62%) and primary responsibility is the mother (86%). The pregnancy was identified by teachers as a topic of interest for continuing education, and least discussed with the students (35.7%) in municipal and (15.7%) in state schools, (p=0.04). Regarding the method of instruction, reading texts and lecture were the most used. Virtually all students have an interest in the topic sexuality. For teachers, students of the municipal schools (80%) know more about prevention and Sexually Transmitted Diseases (STD), compared with the state school (52.2%), (p=0.02) and there is a higher prevalence of pregnancy among students of the state (92.1%) to municipal schools (71.4%) (p=0.03). The theme is present in the PPP for 78.6% of teachers of municipal and 51% of the state, (p=0.01). Recourse available to teachers of the municipal educational was educative material (53.6%) and internet (35.3%) for the state system (p=0.05).To meet the identified needs in this study, was held the First Training Course on Sex Education in the School Context for teachers and delivery of education kits (Reproductive health and sex education). These materials will serve as input for future work on the advice of nurses from the Family Health Strategy (FHS), attached to these educational institutions. The study showed the importance of continuing education for these teachers, as well as benefiting from investments in continuing education teachers in other areas of the city and state. This research has enabled the strengthening of partnerships between government organizations, through the Departments of State and Municipal Education and Health and Higher Education Institution, with a commitment to continuity of government programs such as SPE and SPE.